2004
DOI: 10.22358/jafs/67410/2004
|View full text |Cite
|
Sign up to set email alerts
|

Mutagen-induced chromosome instability in farm animals

Abstract: The frequencies of spontaneous and in vitro mutagen-induced unstable chromosomal lesions were compared in the groups of subfertile cows, ewes and sows (test groups) as well as the animals without any reproductive disturbances (control groups). The mean percentage of 5-azacytidineand bromodeoxyuridine-induced defects differed statistically between the test and control groups (P≤0.01 in cattle, P≤0.05 in sheep and pigs). In the groups of animals with reproductive problems the number of defects observed in some c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Various frequencies of damage within a species have been observed by researchers analysing karyotypes of various breeds of animals (Di Berardino et al 1983;Iannuzzi et al 1991;Riggs et al 1993;Ronne 1995;Di Meo et al 2000;Rodriguez et al 2002;Danielak-Czech and Słota 2004;Peretti et al 2007Peretti et al , 2008Nicodemo et al 2008;Albarella et al 2009;Wójcik et al 2011Wójcik et al , 2012. Differences between mean numbers of various forms of damages in genetic material result from the fact that their frequency is influenced by the breed.…”
Section: Discussionmentioning
confidence: 99%
“…Various frequencies of damage within a species have been observed by researchers analysing karyotypes of various breeds of animals (Di Berardino et al 1983;Iannuzzi et al 1991;Riggs et al 1993;Ronne 1995;Di Meo et al 2000;Rodriguez et al 2002;Danielak-Czech and Słota 2004;Peretti et al 2007Peretti et al , 2008Nicodemo et al 2008;Albarella et al 2009;Wójcik et al 2011Wójcik et al , 2012. Differences between mean numbers of various forms of damages in genetic material result from the fact that their frequency is influenced by the breed.…”
Section: Discussionmentioning
confidence: 99%
“…ranged from 1.5 [35] to 2.9 [36], while in Calabrian it was 6.2, in Large White 4.9, and in Calabrian x Large White crossbreds 4.5 [33]. Our research found 4.8 SCEs/cell and 3.9 FS.…”
Section: Plos Onementioning
confidence: 41%
“…SCEs have been identified in pigs of the breeds Casertana, Calabrian, and Large White; Calabrian x Large White crossbreds; and Nero Siciliano [32][33][34]. FS have been investigated in Landrace, Calabrian and Large White pigs as well as Calabrian x Large White crossbreds [33,35,36]. The frequency of SCEs/cell was reported to be 6.3 [32] and 7.1 [34] in the Casertana breed, 7.3 in Calabrian, 4.5 in Large White, 6.2 in Calabrian x Large White crossbreds [33] and 6.9 in Nero Siciliano [34].…”
Section: Plos Onementioning
confidence: 99%
“…It should be highlighted that the introduction of modern cytomolecular techniques into laboratory practice has considerably increased the diagnostic potential of the screening system, resulting in a marked increase in the number of karyotype abnormalities identified [92,103]. To date, cytogenetic screening of many pig populations around the world has resulted in the identification of over 220 structural karyotype defects, including almost 200 reciprocal translocations with a clear negative impact on fertility and economic efficiency of production [1,2,13,17,19,30,32,41,93,[98][99][100][103][104][105][106][107]. It seems that the elaboration and implementation of the next screening strategies will significantly intensify the detectability of reciprocal translocations, which are likely much more frequent in breeding populations than previously estimated.…”
Section: Cytogenetic Screening Of the Pig Populationmentioning
confidence: 99%